Technology-based business incubators: An exploratory analysis of intra-organizational social networks - Maria Gabriela Miranda; Renata Borges (Innovation & Management Review, 2019)
Purpose: Technology-based incubators depend on high-level knowledge to constantly meet the demands of the market. Incubators offer a variety of specialized services to help startups increase the chances of crossing the valley of death. These services include infrastructure, access to a professional network of mentors and an intensive support of a consultant team to help with managerial and legal challenges. Therefore, it is critical to incubators to develop both highly skilled teams of consultants and social environment that facilitates communication. The purpose of this paper is to understand how innovation-oriented social networks created within technology-based incubators are shaped. Design/methodology/approach: Data were collected in five incubators participating connected to federal universities from the state of Minas Gerais. The network attributes collected in the survey were placed in a matrix form. The mapping and measurement of the relationships between individuals were developed using the Ucinet software. Ucinet enables the analysis of attributes (attitudes, behaviors and characteristics) characterized as relational (contacts, ties and relationships). The software also includes the Netdraw network visualization tool, which enables the creation of matrices and graphical network maps. The measurements of centrality, closeness and intermediation were analyzed to assess the intra-organizational social network. Findings: The results indicate that although the flow of communication does not follow the formal hierarchy, the interaction between team members to spontaneously exchange ideas, information and experiences is rare. The workers are so concerned about their timely tasks, that they have few opportunities to exchange information and knowledge. The coordination is carried out by university professors, who also perform other tasks (e.g. teaching, research and administration activities) besides those related to the incubators. The results also suggest that in the technology-based incubators studied, besides dealing in an innovative environment, the distribution of tasks and responsibilities are still rigid and traditional. Originality/value: By analyzing the degree of the relationship between team members, the proximity and the level of intermediation of co-workers, it is possible to see how the incubators workers interact, thereby identifying the flow of information. This study offers implications for theory and practice. To the theory, this study adds to the discussion of intra-organizational social network of technology-based companies in the Brazilian context. To practitioners, this research sheds light on the importance of the social network built within the organization to promote effective communication and knowledge sharing.
Keywords: 650; Innovation; Social network; Business incubation; Technology-based incubator